2004
DOI: 10.1089/0889222041217419
|View full text |Cite
|
Sign up to set email alerts
|

Multiprotein HIV Type 1 Clade B DNA/MVA Vaccine: Construction, Safety, and Immunogenicity in Macaques

Abstract: Recently, a simian/human immunodeficiency virus (SHIV) vaccine consisting of priming with a Gag-Pol-Env-expressing DNA and boosting with a Gag-Pol-Env-expressing recombinant modified vaccinia Ankara (rMVA) has successfully controlled a virulent SHIV challenge in a macaque model. In this, and the accompanying paper, we report on the construction and testing of a Gag-Pol-Env DNA/MVA vaccine for HIV-1/AIDS. The DNA vaccine, pGA2/JS2, expresses aggregates of Gag proteins and includes safety mutations that render i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 44 publications
4
40
0
Order By: Relevance
“…Consistent with our prior trials using i.m. inoculations of DNA, T-cell responses were not detected until after the first MVA boost (data not shown) (21,34).…”
Section: Resultsmentioning
confidence: 96%
“…Consistent with our prior trials using i.m. inoculations of DNA, T-cell responses were not detected until after the first MVA boost (data not shown) (21,34).…”
Section: Resultsmentioning
confidence: 96%
“…That the recombinant elicited a lesser cell-mediated immune response in macaques perhaps reflects the multiple differences between mouse and human immunology (36), here extended to nonhuman primates. Other studies with rhesus macaques using vectored vaccine candidates have reported widely varying ELISPOT responses to Tat immunogens (30,52). This variability may result from the different vaccine regimens but could also reflect differences in MHC haplotypes.…”
Section: Discussionmentioning
confidence: 99%
“…AF457066) were obtained from the Henry Jackson Modifications of each env gene included (i) removal of the 5TNT early transcription termination signal by silent codon alterations using a site-directed mutagenesis kit (Stratagene, La Jolla, CA) (9), (ii) addition of nucleotides ACC immediately before the initiating ATG for optimal translation (14), and (iii) truncation of the C terminus of the cytoplasmic tail following the sequences GGGEQD, EGGEQG, and EGGEQD for AG, UGD, and KEA env, respectively (34). Three mutations were introduced into the AG gag-pol gene to inactivate reverse transcriptase, strand transfer, and RNase H activities, and the integrase was deleted as previously described (25). The gag-pol genes of UGD and KEA were truncated to delete the RNase H and integrase, and two mutations were made in the active site of the reverse transcriptase.…”
Section: Methodsmentioning
confidence: 99%